1972
DOI: 10.1190/1.1440276
|View full text |Cite
|
Sign up to set email alerts
|

The Analytic Signal of Two‐dimensional Magnetic Bodies With Polygonal Cross‐section: Its Properties and Use for Automated Anomaly Interpretation

Abstract: This paper presents a procedure to resolve magnetic anomalies due to two‐dimensional structures. The method assumes that all causative bodies have uniform magnetization and a cross‐section which can be represented by a polygon of either finite or infinite depth extent. The horizontal derivative of the field profile transforms the magnetization effect of these bodies of polygonal cross‐section into the equivalent of thin magnetized sheets situated along the perimeter of the causative bodies. A simple transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
616
0
98

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,189 publications
(754 citation statements)
references
References 2 publications
2
616
0
98
Order By: Relevance
“…To reduce the extent of the nonuniqueness, it is desirable to determine the shape of the body before calculating its magnetization. The analytic signal technique has been used to delineate sharp magnetic boundaries [e.g., Nabighian, 1972] and thus can be utilized to determine the shape of a magnetic body that is uniformly magnetized [Roest et al, 1992]. We examined the applicability of this technique to the small and isolated magnetic anomalies of Mars by calculating the magnetic anomaly of a vertical prism at altitudes ranging from 50 to 400 km.…”
Section: E03011mentioning
confidence: 99%
“…To reduce the extent of the nonuniqueness, it is desirable to determine the shape of the body before calculating its magnetization. The analytic signal technique has been used to delineate sharp magnetic boundaries [e.g., Nabighian, 1972] and thus can be utilized to determine the shape of a magnetic body that is uniformly magnetized [Roest et al, 1992]. We examined the applicability of this technique to the small and isolated magnetic anomalies of Mars by calculating the magnetic anomaly of a vertical prism at altitudes ranging from 50 to 400 km.…”
Section: E03011mentioning
confidence: 99%
“…In reality, many of 2D geological structures can be approximated by infinite dike and geological contact models which make them more practical than the infinite horizontal cylinder model for interpretation of magnetic and gravity field data (e.g., Nabighian, 1972 and1974;Hsu et al, 1998;Bastani and Pedersen, 2001;Beiki and Pedersen, 2010). Telford et al (1990) and Stanley and Green (1976) have shown expressions for the gravity gradients g xz and g zz caused by infinite dike and geological contact models, respectively.…”
Section: Gravity Gradient Tensormentioning
confidence: 99%
“…The analytic signal A(x) of a potential field x measured along the x-axis at a constant level caused by a 2D body striking along the y-axis can be written as a complex quantity Nabighian (1972Nabighian ( , 1974 showed the application of analytic signal techniques to 2D magnetic interpretation. He (Nabighian, 1984) generalized the 2D analytic signal to 3D and showed that the Hilbert transform of any potential field satisfies the Cauchy-Riemann relations.…”
Section: Analytic Signal Techniquesmentioning
confidence: 99%
“…∂ y representam as primeiras derivadas horizontais do campo magnético, respectivamente nas direções x e y e ∂ M ∂z é a primeira derivada vertical (Nabighian, 1972).…”
Section: Sinal Analíticounclassified